2006
DOI: 10.33338/ef.84349
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic transformation of ground beetle assemblages (Coleoptera: Carabidae) in Bialowieza Forest, Poland: from primeval forests to managed woodlands of various ages

Abstract: The interference of man in the primeval forest of Bialowieza (e. g. clear-cutting and reforesting fertile habitats with pine or spruce) brings about changes in carabid assemblages, including a reduction in the proportion of individuals of relict species, reduction in the mean individual biomass (MIB) and in the sum of positive characteristics (SPC; a summary indicator). Human impact in forest ecosystems causes losses of some relict species and a gain of ubiquitous species. I com— pared the carabid faunas of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 8 publications
1
19
0
1
Order By: Relevance
“…This species is abundant in the forests of South Moravia (Šejnohová, 2006). The species dominates in the forests of Poland (Sklodowski, 2006(Sklodowski, , 2014Kwiatkowski, 2011;Sklodowski & Garbalinska, 2011;Zalewski et al, 2012). There numerous reports of finding this species in Lithuania (Tamutis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This species is abundant in the forests of South Moravia (Šejnohová, 2006). The species dominates in the forests of Poland (Sklodowski, 2006(Sklodowski, , 2014Kwiatkowski, 2011;Sklodowski & Garbalinska, 2011;Zalewski et al, 2012). There numerous reports of finding this species in Lithuania (Tamutis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the proportion of forest species and large zoophages, as well as the MIB index, increased. The latter is a good metric of the successional stage of development of carabid assemblages; a higher value indicates a more advanced stage of regeneration of carabid fauna (Szyszko ; Skłodowski ; Schwerk & Szyszko ). Observations between the first and second year of the study indicated development of the carabid assemblages studied in the plantations.…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of hemizoophages and large zoophages were used in the analyses. The groups based on habitat preferences were forest, eurytopic, and open‐area species; species were assigned to these groups based on earlier observations in Polish forests and on the published literature (Szujecki et al ; Szyszko ; Turin ; Skłodowski ). Forest species were used in the analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic aim of this paper is to trace succession at two post-industrial areas using carabid beetles as indicators (Koivula, 2011). A preliminary analysis of the data collected in the first three years -2006(Schwerk & Szyszko, 2008 revealed that succession was delayed at both heaps. Advanced stages of succession at the sites differed from that recorded at the reference site on natural soil.…”
Section: Introductionmentioning
confidence: 99%